2019
DOI: 10.1128/mra.00765-19
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Staphylococcus aureus Siphophage Sebago

Abstract: Here, we introduce the genome of Sebago, a 43,878-bp siphophage that infects Staphylococcus aureus. Sebago carries 70 proteins and is most closely related to StauST398, a Phietavirus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Accordingly, IEC was significantly enriched in S. aureus genomes of human origin (p < 10 −15 , Fisher's exact test) (Supplementary Figure 1). tarP was usually located on ΦSa3int phages in S. aureus clones harboring the IEC element, whereas it was present on many different phages in S. aureus clones lacking the IEC element, including ΦSa1int, ΦSa2int, ΦSa5int, ΦSa7int, and the newly described ΦSebago (Klotz et al, 2019) that was previously misidentified as Sa9int (Figure 1D) (Gerlach et al, 2018). In addition, we observed that tarP is 40% more frequent in strains lacking the IEC element than in those with IEC (p < 10 −13 by Fisher's exact test), suggesting that tarP is more prevalent in S. aureus clones from non-human animals (Figure 1E).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Accordingly, IEC was significantly enriched in S. aureus genomes of human origin (p < 10 −15 , Fisher's exact test) (Supplementary Figure 1). tarP was usually located on ΦSa3int phages in S. aureus clones harboring the IEC element, whereas it was present on many different phages in S. aureus clones lacking the IEC element, including ΦSa1int, ΦSa2int, ΦSa5int, ΦSa7int, and the newly described ΦSebago (Klotz et al, 2019) that was previously misidentified as Sa9int (Figure 1D) (Gerlach et al, 2018). In addition, we observed that tarP is 40% more frequent in strains lacking the IEC element than in those with IEC (p < 10 −13 by Fisher's exact test), suggesting that tarP is more prevalent in S. aureus clones from non-human animals (Figure 1E).…”
Section: Resultsmentioning
confidence: 96%
“…aureus clones harboring the IEC element, whereas it was present on many different phages in S . aureus clones lacking the IEC element, including ΦSa1int, ΦSa2int, ΦSa5int, ΦSa7int, and the newly described ΦSebago ( Klotz et al, 2019 ) that was previously misidentified as Sa9int ( Figure 1D ) ( Gerlach et al, 2018 ). In addition, we observed that tarP is 40% more frequent in strains lacking the IEC element than in those with IEC ( p < 10 −13 by Fisher’s exact test), suggesting that tarP is more prevalent in S .…”
Section: Resultsmentioning
confidence: 99%